An Annotated Translation of Janet Dailey’s Savage Land - Astuti, Retno Budi; Djohan, Rita Sutjiati (Universitas Gunadarma, 2014)
This is an annotated translation research. The problems of the research are: (1) What are the difficulties/problems encountered by the researcher when translating the source text? (2) How does the researcher cope/handle with the problems in order to get the solutions? The purposes of this research are: (1) To find out the difficulties/problems encountered by the researcher when translating the source text. (2) To describe the way the researcher copes with the problems in order to get the solutions and to solve the problems encountered by the researcher when translating the source text. The method used in this study is introspective and retrospective methods. Relevant translation strategies and theories are used in solving the problems that are encountered during the translation. Results obtained from this research show that there are 1 phrasal verb, 1 auxiliary, 1 clause, 1 phrase, 2 prepositions, 14 words, 3 pronouns, and 2 idiomatic expressions from 25 data analyzed that pose difficulty to be translated by the researcher/translator. Based on the 25 data which have been analyzed, it was found that there are 11 translation strategies used by the researcher to solve the problems/difficulties in translating the source text into the target text, namely 1 calque, 1 literal translation, 1 interpersonal change, 1 loan, 2 phrase structure changes, 2 paraphrases, 2 distribution changes, 3 explicitness changes, 4 abstraction changes, 2 cohesion changes, and 6 naturalizations.Keywords: annotated translations, problems, solutions.